UJI MODEL HUBUNGAN DARK TRIAD TRAITS DENGAN HUMOR STYLE DAN SCHADENFREUDE - Dendy Maulana Rahman; Ananta Yudiarso (CALYPTRA, 2024)
Abstract—This research explores the relationship between dark triad traits, humor style, and schadenfreude. The participants in the study consisted of 302 undergraduate students ranging from early to final semesters, aged over 17 years, selected using accidental sampling technique. Measurements were conducted using the Short Dark Triad Traits Scale (SD3), the Humor Style Questionnaire (HSQ), and the Schadenfreude Scale. The results of the model test indicate that individuals with dark triad traits, particularly psychopathy, tend to adopt an aggressive humor style and experience schadenfreude. Future research is recommended to compare two population groups using direct and indirect effect analysis and bootstrapping methods. This could provide a deeper insight into the impact of dark triad traits on humor style and schadenfreude. Keywords: dark triad traits, humor style, schadenfreude Abstrak—Penelitian ini membahas hubungan dark triad traits dengan humor style dan schadenfreude. Partisipan dalam penelitian 302 mahasiswa semester awal hingga semester akhir di atas 17 tahun dengan teknik sampling accidental. Pengukuran menggunakan skala short dark triad traits (SD3), humor style questionnaire (HSQ), Skala Schadenfreude. Hasil uji model menunjukan individu dengan dark triad traits khususnya psikopati cenderung mengadopsi aggressive humor style dan mengalami schadenfreude. Penelitian mendatang disarankan untuk membandingkan dua kelompok populasi dengan analisis direct and indirect effect dan metode bootstrapping. Ini dapat memberikan wawasan lebih mendalam tentang dampak dark triad traits terhadap humor style dan schadenfreude. Kata kunci: dark triad traits, humor style, schadenfreude